Thermodynamic studies and parametric effects on exergetic performance of a steam power plant. Issue 1 (2nd January 2019) - Kumar, Vinay; Pandya, Bhargav; Matawala, Vijay
ABSTRACT: A comprehensive thermodynamic analysis is conducted for an existing 82 MW steam power plant. A detailed assessment on energy loss and exergy destruction for individual components of plants (including boiler sub-parts) is reported. A code is built in EES to evaluate the energy loss, energy efficiency, physical and chemical exergies, exergy efficiency and exergy destruction for each part of plant by considering the real values' range of operating parameters. Analysis pointed out that the main sources of exergy destruction are boilers followed by the turbines, deaerators and then condensers. In boiler, combustor contributes about 50% in total exergy destruction. The maximum energy loss is reported in boilers followed by condensers, in piping, due to friction and in turbines. The exergy efficiency procured about 42% for boilers, 84% for turbines, 38% for condenser, and 60% for deaerators, respectively. The effects of crucial working parameters on plant performance are analysed.